Advances in Hyaluronic Acid for Biomedical Applications - Yasin, Aqeela; Ren, Ying; Li, Jingan; Sheng, Yulong; Cao, Chang; Zhang, Kun (Frontiers in Bioengineering and Biotechnology, 2022)
Hyaluronic acid (HA) is a large non-sulfated glycosaminoglycan that is the main component of the extracellular matrix (ECM). Because of its strong and diversified functions applied in broad fields, HA has been widely studied and reported previously. The molecular properties of HA and its derivatives, including a wide range of molecular weights but distinct effects on cells, moisture retention and anti-aging, and CD44 targeting, promised its role as a popular participant in tissue engineering, wound healing, cancer treatment, ophthalmology, and cosmetics. In recent years, HA and its derivatives have played an increasingly important role in the aforementioned biomedical fields in the formulation of coatings, nanoparticles, and hydrogels. This article highlights recent efforts in converting HA to smart formulation, such as multifunctional coatings, targeted nanoparticles, or injectable hydrogels, which are used in advanced biomedical application.